2018
DOI: 10.1002/pon.4906
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported health‐related quality of life outcomes in supportive‐care interventions for adults with brain tumors: A systematic review

Abstract: Objectives The objectives of this systematic review were to (a) identify supportive‐care (psychosocial/behavioral, pharmacological, complementary, or alternative) interventions that have been evaluated via randomized controlled trials (RCTs) to improve patient‐reported health‐related quality of life (HRQoL) among adults with brain tumors, (b) evaluate the quality of the intervention studies, and (c) evaluate if developed interventions have been efficacious at improving HRQoL, as compared with control condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 75 publications
2
28
0
Order By: Relevance
“…19 Improvement across a range of symptoms can significantly influence QoL, and reviews indicate that acupuncture benefits QoL in palliative care. 57,74 Seven articles were found that discuss safety of acupuncture in palliative care. 50,53,60,63,64,68,75 Filshie focuses on addressing safety issues 75 ; the other articles generally conclude that acupuncture can be a safe procedure in palliative care if administered by qualified practitioners, provided key safety issues are addressed, 50,53,63,64,68 similarly for children.…”
Section: Evidence For Acupuncture In Palliative Carementioning
confidence: 99%
“…19 Improvement across a range of symptoms can significantly influence QoL, and reviews indicate that acupuncture benefits QoL in palliative care. 57,74 Seven articles were found that discuss safety of acupuncture in palliative care. 50,53,60,63,64,68,75 Filshie focuses on addressing safety issues 75 ; the other articles generally conclude that acupuncture can be a safe procedure in palliative care if administered by qualified practitioners, provided key safety issues are addressed, 50,53,63,64,68 similarly for children.…”
Section: Evidence For Acupuncture In Palliative Carementioning
confidence: 99%
“…In recent international palliative care guidelines for adults with glioma (Pace et al, ), the MAST program was endorsed as showing clinically significant benefits for managing depression, with the quality of evidence rated higher than for pharmacological interventions. Further, in a systematic review of 10 RCTs of interventions for adults with brain tumour (Pan‐Weisz et al, ), MAST was the only psychosocial program associated with significant improvements in QoL relative to control conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from hospital-based care to the community is a period of heightened vulnerability for psychological distress, as the diverse physical, cognitive and behavioural effects of the illness become more apparent and contact with health professionals diminishes (Ownsworth et al, 2011). Although clinical practice guidelines for oncology emphasize the need to routinely screen people for distress, provide appropriate interventions and follow-up (Jacobsen & Lee, 2015), there is limited research on psychosocial support interventions for individuals with brain tumour and their families (Pan-Weisz et al, 2019). The mode of delivery is a priority consideration given that many experience debilitating physical and cognitive symptoms which affect their eligibility to drive and access community-based support in the usual ways (Halkett et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In international palliative care guidelines for adults with glioma (Pace et al, 2017), the quality of evidence for the MAST intervention was rated as higher than pharmacological interventions for managing mood disorders. In a subsequent review of supportive care for brain tumour (Pan-Weisz et al, 2019), the MAST programme was found to be the only psychosocial intervention associated with improvements in QoL. Other rehabilitation interventions have shown evidence of gains in cognitive or physical functioning, but these have not extended to improvements in emotional functioning or QoL (Boele et al, 2018;Gehring et al, 2009).…”
Section: Introductionmentioning
confidence: 99%